Imaging the multiple sclerosis lesion: insights into pathogenesis, progression and repair. Issue 3 (June 2019) - Wang, Chenyu Tim; Barnett, Michael; Barnett, Yael
Abstract : Purpose of review: Focal white matter lesions are the defining pathological and imaging hallmark of the multiple sclerosis. Until recently, elucidation of the pathophysiology of lesion formation, progression and repair has relied on point neuropathological observations. Here, we review current and emerging concepts of the MRI-defined multiple sclerosis lesion phenotype, advanced longitudinal imaging techniques that permit in-vivo exploration of dynamic microstructural change within lesions and emerging MRI measures of lesion repair. Recent findings: Novel MRI techniques have elucidated dynamic features of the active multiple sclerosis lesion, defined imaging surrogates for chronic active lesions and revealed progressive microstructural change within chronic inactive lesions. Lesion-related anterograde, retrograde and trans-synaptic neurodegenerative mechanisms are being unravelled in vivo through MRI. An array of myelin-imaging techniques have emerged and in some cases have already been integrated into Phase 2 remyelination trials. Summary: MRI has shed new light on dynamic processes that occur over the lifespan of the multiple sclerosis lesion, and reaffirms the critical role of focal pathology as a determinant of disease progression. The development of robust, longitudinal biomarkers of lesion microstructure, such as advanced diffusion imaging, will be especially important as the era of neurorepair trials in multiple sclerosis dawns.